Moxibustion Inhibits the Expression of Colonic NLRP3 through miR7/RNF183/NF-κB Signaling Pathway in UC Rats. (3rd November 2021) - Li, Xi-Ying; Yang, Yan-Ting; Zhao, Yue; Kong, Xie-He; Yang, Guang; Hong, Jue; Zhang, Dan; Ma, Xiao-Peng
Abstract : Background . Moxibustion has been recognized as an effective approach for ulcerative colitis, yet its mechanism is not clear. The research aimed to investigate the influence of moxibustion on the activation of NLRP3 inflammasome and its mechanism in treating ulcerative colitis by observing miR7/RNF183 inducing I κ B α ubiquitination to regulate NF- κ B signaling pathway in an ulcerative colitis rat model. Methods . An ulcerative colitis rat model was established by unlimited access to self-administration of 3.5% (w/v) dextran sulfate sodium solution. Mild moxibustion was applied to bilateral Tianshu points (ST25) in the moxa-stick moxibustion group; rats in the control group were intervened by intraperitoneal injection of ubiquitination inhibitor, MG132. The disease activity index was determined at the end of the intervention; colon injury was observed and scored after hematoxylin-eosin staining; the immunohistochemical method was adopted to detect the expressions of colonic IL-1 β and NLRP3 proteins; Western blot determined the expressions of RNF183, I κ B α, and NF- κ B p65 proteins in the colon; the immunofluorescence test was used to observe the coexpression of I κ B α /ubiquitin and I κ B α /RNF183 proteins in the colon; immunoprecipitation assay was adopted to observe the interaction between I κ B α and RNF183 proteins; and quantitative real-time polymerase chain reaction determined the expression of colonic miR7. Results . Moxibustion lowered the disease activity index, manifesting as restored colonic tissue and reduced inflammatory reaction, and decreased expression levels of NLRP3 and IL-1 β proteins, compared with the model group. It also reduced colonic expression of NF- κ B p65 protein, together with the increased level of I κ B α protein and weaker expression levels of ubiquitin and RNF183 proteins and mRNAs and stronger expression of miR7. There were no significant differences between the moxa-stick moxibustion group and the control group except the expressions of RNF183 protein and mRNA and miR7. Conclusion . Moxibustion encourages the recovery of colon injury probably by regulating the expression of NLRP3 protein in ulcerative colitis rats through miR7/RNF183/NF- κ B signaling pathway.